Examining a device for air distribution by the interaction of counter non-coaxial jets under alternating mode - Коrbut Vadim; Voznyak, Orest; Myroniuk, Khrystyna; Sukholova, Iryna; Kapalo, Peter (Eastern-European Journal of Enterprise Technologies, 2017)
The research deals with the solution of the relevant problem of increasing efficiency of air distribution by the interaction of counter non-coaxial jets for providing the standard parameters of the air in industrial premises. The mathematical model of air supply by the interaction of counter non-coaxial jets in these premises was improved. It was shown that to achieve maximum efficiency of air disctribution, it is necessary to supply the air by jets that attenuate rapidly even before entering the working area. We developed and explored the structure of the air distributor with the interaction of the counter non-coaxial jets, which provides intensive attenuation of velocity and excess temperature of the resulting airflow. The specific feature of this structure is the possibility to supply two non-coaxial inflowing jets. In this way, intensive mixing of inflowing jets with the surrounding air is provided and alternating mode is maintained. The graphic dependences were plotted and the theoretical dependences based on the conducted experimental studies were derived, which may be used in further engineering calculations. The authors developed and protected by the patent of Ukraine [12] the design of air distributor for the air supply by the interaction of the counter non-coaxial jets, as well as for supplying inflowing jets in the alternating mode. The cost-effectiveness of using the air distributor with the interaction of counter non-coaxial jets was shown, compared with alternative options, and specific indicators of the air distribution efficiency were given.